A particle is executing SHM of amplitude A, about the mean position x=0. Which of the following is a possible phase difference between the positions of the particle at $x = + \dfrac{A}{2}$ and $x = - \dfrac{A}{{\sqrt 2 }}$’.
A) ${75^\circ }$
B) ${165^\circ }$
C) ${135^\circ }$
D) ${195^\circ }$
Answer
Verified
123k+ views
Hint: In this question we have to find the phase difference between the positions of the particle at $x = + \dfrac{A}{2}$ and $x = - \dfrac{A}{2}$. For this we are going to use the equation of Simple Harmonic Motion and then put the values of the positions and find the value of phase difference between those positions.
Complete step by step solution:
Given,
Positions- $x = + \dfrac{A}{2}$and $x = - \dfrac{A}{2}$
The equation of Simple Harmonic Motion (SHM) is given below;
$x = A\cos (\omega t + \phi )$
Where, x is the position and
$\omega $ is angular frequency
$\phi $ is the phase difference
Let the phase difference of first position is ${\phi _1}$ and the phase difference of second position is ${\phi _2}$.
Now, putting the values of positions and phase difference in the above equations of simple harmonic motion;
When $x = \dfrac{A}{2}$ the equation of motion becomes,
$\dfrac{A}{2} = A\cos (\omega t + {\phi _1})$….. (1)
When $x = - \dfrac{A}{{\sqrt 2 }}$the equation of motion becomes,
$\Rightarrow - \dfrac{A}{{\sqrt 2 }} = A\cos (\omega t + {\phi _2})$….. (2)
From equation (1)
$\Rightarrow \dfrac{1}{2} = \cos (\omega t + {\phi _1})$
$\Rightarrow {\cos ^{ - 1}}\left( {\dfrac{1}{2}} \right) = (\omega t + {\phi _1})$
$\Rightarrow 60^\circ = (\omega t + {\phi _1})$….. (3)
From equation (2)
$ \Rightarrow - \dfrac{1}{{\sqrt 2 }} = \cos (\omega t + {\phi _2})$
$\Rightarrow {\cos ^{ - 1}}\left( { - \dfrac{1}{{\sqrt 2 }}} \right) = (\omega t + {\phi _2})$
$\Rightarrow 45^\circ = (\omega t + {\phi _2})$….. (4)
Phase difference ${\phi _2} - {\phi _1} = 60^\circ - 45^\circ $
$\Rightarrow {\phi _2} - {\phi _1} = 15^\circ $
Now, if we consider the equation of simple harmonic motion in terms of sine then the equation of motion is given by,
$\Rightarrow x = A\sin (\omega t + \phi )$
Now, putting the values of positions and phase difference in the above equations of simple harmonic motion;
When $x = \dfrac{A}{2}$ the equation of motion becomes,
$\Rightarrow \dfrac{A}{2} = A\sin (\omega t + {\phi _1})$….. (5)
When $x = - \dfrac{A}{{\sqrt 2 }}$the equation of motion becomes,
$\Rightarrow - \dfrac{A}{{\sqrt 2 }} = A\sin (\omega t + {\phi _2})$….. (6)
From equation (5)
$\Rightarrow \dfrac{1}{2} = \sin (\omega t + {\phi _1})$
$\Rightarrow {\sin ^{ - 1}}\left( {\dfrac{1}{2}} \right) = (\omega t + {\phi _1})$
$\Rightarrow 30^\circ = (\omega t + {\phi _1})$….. (7)
From equation (6)
$\Rightarrow - \dfrac{1}{{\sqrt 2 }} = \sin (\omega t + {\phi _2})$
$\Rightarrow {\sin ^{ - 1}}\left( { - \dfrac{1}{{\sqrt 2 }}} \right) = (\omega t + {\phi _2})$
$\Rightarrow 225^\circ = (\omega t + {\phi _2})$….. (4)
Phase difference ${\phi _2} - {\phi _1} = 225^\circ - 30^\circ $
$\Rightarrow {\phi _2} - {\phi _1} = 195^\circ $
Result- Hence, from above calculation we have seen that the phase difference between the positions $x = + \dfrac{A}{2}$ and $x = - \dfrac{A}{{\sqrt 2 }}$ is ${\phi _2} - {\phi _1} = 195^\circ $.
Note: In this question we have used the equation of motion for simple harmonic motion, for this we should have the knowledge of simple harmonic motion. Simple harmonic motion is a type of periodic motion where the restoring force on the moving object is directly proportional to the magnitude of the displacement of the object and the direction of restoring force is towards the mean position of the object.
Complete step by step solution:
Given,
Positions- $x = + \dfrac{A}{2}$and $x = - \dfrac{A}{2}$
The equation of Simple Harmonic Motion (SHM) is given below;
$x = A\cos (\omega t + \phi )$
Where, x is the position and
$\omega $ is angular frequency
$\phi $ is the phase difference
Let the phase difference of first position is ${\phi _1}$ and the phase difference of second position is ${\phi _2}$.
Now, putting the values of positions and phase difference in the above equations of simple harmonic motion;
When $x = \dfrac{A}{2}$ the equation of motion becomes,
$\dfrac{A}{2} = A\cos (\omega t + {\phi _1})$….. (1)
When $x = - \dfrac{A}{{\sqrt 2 }}$the equation of motion becomes,
$\Rightarrow - \dfrac{A}{{\sqrt 2 }} = A\cos (\omega t + {\phi _2})$….. (2)
From equation (1)
$\Rightarrow \dfrac{1}{2} = \cos (\omega t + {\phi _1})$
$\Rightarrow {\cos ^{ - 1}}\left( {\dfrac{1}{2}} \right) = (\omega t + {\phi _1})$
$\Rightarrow 60^\circ = (\omega t + {\phi _1})$….. (3)
From equation (2)
$ \Rightarrow - \dfrac{1}{{\sqrt 2 }} = \cos (\omega t + {\phi _2})$
$\Rightarrow {\cos ^{ - 1}}\left( { - \dfrac{1}{{\sqrt 2 }}} \right) = (\omega t + {\phi _2})$
$\Rightarrow 45^\circ = (\omega t + {\phi _2})$….. (4)
Phase difference ${\phi _2} - {\phi _1} = 60^\circ - 45^\circ $
$\Rightarrow {\phi _2} - {\phi _1} = 15^\circ $
Now, if we consider the equation of simple harmonic motion in terms of sine then the equation of motion is given by,
$\Rightarrow x = A\sin (\omega t + \phi )$
Now, putting the values of positions and phase difference in the above equations of simple harmonic motion;
When $x = \dfrac{A}{2}$ the equation of motion becomes,
$\Rightarrow \dfrac{A}{2} = A\sin (\omega t + {\phi _1})$….. (5)
When $x = - \dfrac{A}{{\sqrt 2 }}$the equation of motion becomes,
$\Rightarrow - \dfrac{A}{{\sqrt 2 }} = A\sin (\omega t + {\phi _2})$….. (6)
From equation (5)
$\Rightarrow \dfrac{1}{2} = \sin (\omega t + {\phi _1})$
$\Rightarrow {\sin ^{ - 1}}\left( {\dfrac{1}{2}} \right) = (\omega t + {\phi _1})$
$\Rightarrow 30^\circ = (\omega t + {\phi _1})$….. (7)
From equation (6)
$\Rightarrow - \dfrac{1}{{\sqrt 2 }} = \sin (\omega t + {\phi _2})$
$\Rightarrow {\sin ^{ - 1}}\left( { - \dfrac{1}{{\sqrt 2 }}} \right) = (\omega t + {\phi _2})$
$\Rightarrow 225^\circ = (\omega t + {\phi _2})$….. (4)
Phase difference ${\phi _2} - {\phi _1} = 225^\circ - 30^\circ $
$\Rightarrow {\phi _2} - {\phi _1} = 195^\circ $
Result- Hence, from above calculation we have seen that the phase difference between the positions $x = + \dfrac{A}{2}$ and $x = - \dfrac{A}{{\sqrt 2 }}$ is ${\phi _2} - {\phi _1} = 195^\circ $.
Note: In this question we have used the equation of motion for simple harmonic motion, for this we should have the knowledge of simple harmonic motion. Simple harmonic motion is a type of periodic motion where the restoring force on the moving object is directly proportional to the magnitude of the displacement of the object and the direction of restoring force is towards the mean position of the object.
Recently Updated Pages
The ratio of the diameters of two metallic rods of class 11 physics JEE_Main
What is the difference between Conduction and conv class 11 physics JEE_Main
Mark the correct statements about the friction between class 11 physics JEE_Main
Find the acceleration of the wedge towards the right class 11 physics JEE_Main
A standing wave is formed by the superposition of two class 11 physics JEE_Main
Derive an expression for work done by the gas in an class 11 physics JEE_Main
Trending doubts
JEE Mains 2025: Check Important Dates, Syllabus, Exam Pattern, Fee and Updates
JEE Main Login 2045: Step-by-Step Instructions and Details
Class 11 JEE Main Physics Mock Test 2025
JEE Main Chemistry Question Paper with Answer Keys and Solutions
JEE Main Exam Marking Scheme: Detailed Breakdown of Marks and Negative Marking
JEE Main 2023 January 24 Shift 2 Question Paper with Answer Keys & Solutions
Other Pages
JEE Advanced Marks vs Ranks 2025: Understanding Category-wise Qualifying Marks and Previous Year Cut-offs
NCERT Solutions for Class 11 Physics Chapter 1 Units and Measurements
NCERT Solutions for Class 11 Physics Chapter 9 Mechanical Properties of Fluids
Units and Measurements Class 11 Notes: CBSE Physics Chapter 1
JEE Advanced 2025: Dates, Registration, Syllabus, Eligibility Criteria and More
NCERT Solutions for Class 11 Physics Chapter 2 Motion In A Straight Line